Hemochromatosis mutations in the general population: iron overload progression rate - Andersen, Rolf Værn; Tybjærg-Hansen, Anne; Appleyard, Merete; Birgens, Henrik; Nordestgaard, Børge Grønne (Blood, 2004)
The progression rate of iron overload in hereditary hemochromatosis in individuals in the general population is unknown. We therefore examined in the general population iron overload progression rate in C282Y homozygotes. Using a cohort study of the Danish general population, The Copenhagen City Heart Study, we genotyped 9174 individuals. The 23 C282Y homozygotes identified were matched to 2 subjects each of 5 otherHFEgenotypes with respect to sex, age, and alcohol consumption. As a function of biologic age, transferrin saturation increased from 50% to 70% from 25 to 85 years of age and from 70% to 80% from 35 to 80 years of age in female and male C282Y homozygotes, respectively. Equivalently, ferritin levels increased from 100 to 500 μg/L and decreased from 800 to 400 μg/L in female and male C282Y homozygotes. As a function of 25 years follow-up irrespective of age, transferrin saturation and ferritin levels increased slightly in male and female C282Y homozygotes. None of the C282Y homozygotes developed clinically overt hemochromatosis. In conclusion, individuals in the general population with C282Y homozygosity at most demonstrate modest increases in transferrin saturation and ferritin levels, and clinically overt hemochromatosis is rare. Therefore, C282Y homozygotes identified during population screening, and not because of clinically overt hemochromatosis, at most need to be screened for manifestations of hemochromatosis every 10 to 20 years. (Blood. 2004;103: 2914-2919)